2010
DOI: 10.1094/cchem-87-3-0190
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Corn Lines with Increased Resistant Starch and Impact on Starch Thermal Characteristics

Abstract: Ten parent corn lines, including four mutants (dull sugary2, amyloseextender sugary2, amylose-extender dull, and an amylose-extender with introgressed Guatemalen germplasm [GUAT ae]) and six lines with introgressed exotic germplasm backgrounds, were crossed with each other to create 20 progeny crosses to increase resistant starch (RS) as a dietary fiber in corn starch and to provide materials for thermal evaluation. The resistant starch 2 (RS2) values from the 10 parent lines were 18.3-52.2% and the values fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…RS measured by the Megazyme RS kit is RS2 because the starch used in the analysis is not gelatinized, so our positive correlation between RS and T o g would have a similar explanation. Rohlfing et al (2010) found a correlation between their measurement of RS2 and H g but were unable to …”
Section: Correlation Of Starch Thermal Properties With Rsmentioning
confidence: 90%
See 3 more Smart Citations
“…RS measured by the Megazyme RS kit is RS2 because the starch used in the analysis is not gelatinized, so our positive correlation between RS and T o g would have a similar explanation. Rohlfing et al (2010) found a correlation between their measurement of RS2 and H g but were unable to …”
Section: Correlation Of Starch Thermal Properties With Rsmentioning
confidence: 90%
“…Rohlfing et al (2010) found correlation between peak temperature of gelatinization (T p g ) and RS, attributing the correlation to the presence of RS2 that would delay gelatinization. RS measured by the Megazyme RS kit is RS2 because the starch used in the analysis is not gelatinized, so our positive correlation between RS and T o g would have a similar explanation.…”
Section: Correlation Of Starch Thermal Properties With Rsmentioning
confidence: 94%
See 2 more Smart Citations
“…However, for RS, environmental variation component is difficult to predict and control compared to genetic variation (Birt et al, 2013). Genetic variation occurs within botanical sources due to allelic variation in the starch biosynthetic genes as is the case in commercial maize varieties, which exhibit little variation in resistant starch levels (Rohlfing et al, 2010;Pollack et al, 2011). This variation in RS content was observed in our study genotypes with some recording upto 5 folds more RS than others when grown in the same site (Table 4).…”
Section: Wheat Varietiesmentioning
confidence: 99%